THỬ NGHIỆM ĐÁNH GIÁ HIỆU QUẢ CỦA MỘT SỐ LOẠI SƠN CHỐNG HÀ TIÊU BIỂU CHO TÀU BIỂN - Nguyễn, Văn Chi; Đồng, Văn Kiên; Bùi, Bá Xuân; Mai, Văn Minh; Phan, Bá Tứ; Nguyễn, Văn Triều (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
VALUATION OF THE EFFECIENCY OF SOME POPULAR ANTI-FOULING PAINTS IN VIETNAM BY SEAWATER IMMERSION TESTING In this study, six anti-fouling paints available in Vietnam (01 by Jotun, 05 by other Vietnamese companies) have been studied. The testing results showed that Jotun, Hai Van and The He Moi anti-fouling paints had relatively higher initial adhesion than that of Hai Au, Hai Phong and Dong A anti-fouling paints. After 35 days immersed in seawater, the adhesion of the first group paints had tended to decrease faster than that of the second group paints, although the values of their absolute adhesion are still higher. Jotun and Hai Au paints showed good anti-fouling and anti-corrosion properties after 27 months. The other paints maintain their high level of effectiveness in 21 months. After 21 months, the fouling process began to take place and reached 10% of sample area after 27 months.